Características personales individuales y resultados del comportamiento organizacional en la municipalidad distrital de Curgos, provincia Sánchez Carrión - año 2015 - Flores Marceliano, Sandra Magaly (2016)
This thesis has been done in the City of Curgos province Sanchez Carrion, La Libertad, Peru; its aim is to explain m Director that they influence the Individual Personal Characteristics in Organizational Behavior Results in the District Municipality of Curgos. After The Reality Check problematic, has formulated the research question: How does the Personal Characteristics Individual influence the results of Organizational Behavior in the District Municipality of Curgos, Sanchez Carrion Province - Year 2015? To collect the data have to be looked at two populations, which are Be Small Samples Same Study: Managers of different areas (15) and city manager (01). To collect information they have been implemented surveys and interviews. Obtaining the results, and following the scientific method has been performed the analysis and discussion, getting to demonstrate the validity of the hypothesis: "The individual personal characteristics significantly influence on the results of Organizational Behavior in the District Municipality of Curgos, Province Sanchez Carrion Year 2015" Finally conclusions and recommendations have been formulated. The main conclusion states that the results generally qualify Organizational Behavior with 62.8 points (based on 100); dimensions according to the most favorable score are: satisfaction charge (86.7) , productivity (63.3), innovation (66.7 and 60.0), and limited absenteeism (60.0); and an unfavorable dimension : high turnover of senior management (40.0 points). It is recommended to apply policies respecting differences of people and avoid favoritism by age, gender, marital status or religion; require professional, technical and psychological abilities of people entering ; Results should be evaluated Organizational Behavior, seeking to raise its rating on all of the lower dimensions of management turnover and absenteeism, and less productivity, innovation, and satisfaction in office.